ICF Core Sets for individuals with spinal cord injury in the early post-acute context - I. Kirchberger (2018)
Study design:A formal decision-making and consensus process integrating evidence gathered from preparatory studies was followed.Objectives:The aim of this study was to report on the results of the consensus process to develop the first version of a Comprehensive International Classification of Functioning, Disability and Health (ICF) Core Set and a Brief ICF Core Set for individuals with spinal cord injury (SCI) in the early post-acute context.Setting:The consensus conference took place in Switzerland. Preparatory studies were performed worldwide.Methods:Preparatory studies included an expert survey, a systematic literature review, a qualitative study and empirical data collection involving people with SCI. ICF categories were identified in a formal consensus process by international experts from different backgrounds.Results:The preparatory studies identified a set of 531 ICF categories at the second, third and fourth levels. From 30 countries, 33 SCI experts attended the consensus conference (11 physicians, 6 physical therapists, 5 occupational therapists, 6 nurses, 3 psychologists and 2 social workers). Altogether 162 second-, third- or fourth-level categories were included in the Comprehensive ICF Core Sets with 63 categories from the component Body Functions, 14 from Body Structures, 53 from Activities and Participation and 32 from Environmental Factors. The Brief Core Set included a total of 25 second-level categories with 8 on Body Functions, 3 on Body Structures, 9 on Activities and Participation, and 5 on Environmental Factors.Conclusion:A formal consensus process-integrating evidence and expert opinion based on the ICF led to the ICF Core Sets for individuals with SCI in the early post-acute context. Further validation of this first version is needed. © 2010 International Spinal Cord Society All rights reserved.